(untitled) (Bioresearch Communications, 2023)
A lipoma is a benign tumor of fatty tissues. It is usually harmless; however, may sometimes need laboratory examinations to confirm diagnosis. Conventional medicines are mostly ineffective in diminishing fat spar, therefore surgical removal is preferred. This article is to report case studies of two individuals of a fairly large lipoma, which were treated with ultra-diluted atropine belladonna. In both cases the lipoma wall punctured within few days, drained all the debris and healed lesion surface observed within four weeks. This alternative treatment evidenced that ultra-diluted atropine belladonna may have significant role in lipoma management. More extensive research is needed to understand the mode of action of ultra-diluted atropine belladonna in managing lipomas. Bioresearch Commu. 9(2): 1357-1360, 2023 (July)